The Boy Inventor's Wireless Triumph - Bonner, Richard; Wrenn, Charles L. (Charles Lewis), 1880-1952 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Boy Inventor$1 (Bs Wireless Triumph" by Richard Bonner is a children's adventure novel written in the early 20th century. The story centers around two young inventors, Jack Chadwick and his cousin Tom Jesson, as they embark on a thrilling journey fueled by their shared love for science and exploration. Set against the backdrop of wireless technology and adventure in the Gulf of Mexico, the boys are drawn into a mysterious incident involving their father's yacht and a series of perilous challenges. The opening of the book establishes a vibrant setting on Lone Island, where Jack and Tom are experimenting with their wireless station when they receive a cryptic urgent message indicating that someone is in danger. With a sense of excitement and urgency, the boys quickly prepare to set sail on their motor cruiser, the Vagrant, to respond to the call for help. As they rush into action, the narrative hints at their past collaborative experiences in inventing and their strong familial ties, setting the stage for their impending adventure. Jack$1 (Bs ingenuity and Tom$1 (Bs engineering skills promise an engaging journey filled with scientific intrigue, danger, and the quest for rescue. (This is an automatically generated summary.)s
Release date is 2016-10-17
Produced by Roger Frank
Keywords: Telegraph, Wireless -- Juvenile fiction; Inventors -- Juvenile fiction